2012
DOI: 10.1589/jpts.24.667
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Rollators with Forearm Support on Walking Speed, Endurance and Dynamic Balance

Abstract: Abstract.[Purpose] The purpose of this study was to measure the effect of structural components on walking ability by conducting tests using subjects who used combined rollator-wheelchairs and walking aids in their daily lives.[Subjects] Ten residents living in a health care facility for the elderly who required walking aids participated in this study.[Methods] We measured maximum walking speed (MWS), step length, cadence and conducted the shuttle stamina walk test (SSTw), and the timed up-and-go test (TUG) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The conflicting results of earlier studies on the use of walking aid devices may be due to the different types of walkers used. Daisuke Fujita et al 11 ) compared the walking of people who used a rollator with forearm support and those who used a rollator with a handgrip and cart. They found that the gait speed was greater for people who used a rollator with forearm support and that changes in walking characteristics were observed for different types of walking aid devices.…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting results of earlier studies on the use of walking aid devices may be due to the different types of walkers used. Daisuke Fujita et al 11 ) compared the walking of people who used a rollator with forearm support and those who used a rollator with a handgrip and cart. They found that the gait speed was greater for people who used a rollator with forearm support and that changes in walking characteristics were observed for different types of walking aid devices.…”
Section: Discussionmentioning
confidence: 99%